Femur Length is Correlated with Isometric Quadriceps Strength in Post-Operative Patients - Robert S Dean; Nicholas N DePhillipo; Michael T Kiely; Nicole A Schwery; Jill K Monson; Robert F LaPrade (North American Sports Medicine Institute, 2022)
# BACKGROUND Few existing studies have examined the relationship between lower extremity bone length and quadriceps strength. # PURPOSE/HYPOTHESIS To evaluate the relationship between lower extremity, tibia and femur lengths, and isometric quadriceps strength in patients undergoing knee surgery. The null hypothesis was that there would be no correlation between lower extremity length and isometric quadriceps strength. # STUDY DESIGN Cross-sectional study # METHODS Patients with full-length weightbearing radiographs that underwent isometric quadriceps strength testing after knee surgery were included. Using full-length weightbearing radiographs, limb length was measured from the ASIS to the medial malleolus; femur length was measured from the center of the femoral head to the joint line; tibia length was measured from the center of the plateau to the center of the plafond. Isometric quadriceps strength was measured using an isokinetic dynamometer. Pearson's correlation coefficient was used to report the correlation between radiographic limb length measurements. A Bonferroni correction was utilized to reduce the probability of a Type 1 error. # RESULTS Forty patients (26 males, 14 females) with an average age of 25.8 years were included. The average limb, femur, and tibia lengths were not significantly different between operative and non-operative limbs (p>0.05). At an average of 5.8±2.5 months postoperatively, the peak torque (156.6 vs. 225.1 Nm), average peak torque (151.6 vs. 216.7 Nm), and peak torque to bodyweight (2.01 vs 2.89 Nm/Kg) were significantly greater in the non-surgical limb (p<0.01). Among ligament reconstructions there was a significant negative correlation between both limb length and strength deficit (r= -0.47, p=0.03) and femur length and strength deficit (r= -0.51, p=0.02). The average strength deficit was 29.6% among the entire study population; the average strength deficit was 37.7% among knee ligament reconstructions. For the non-surgical limb, femur length was significantly correlated with peak torque (r = 0.43, *p* = 0.048). # CONCLUSION Femur length was significantly correlated with the isometric quadriceps peak torque for non-surgical limbs. Additionally, femur length and limb length were found to be negatively correlated with quadriceps strength deficit among ligament reconstruction patients. A combination of morphological features and objective performance metrics should be considered when developing individualized rehabilitation and strength programs.